Building a Global Legal Culture: Anticipating Climate Change - Maerani, Ira Alia (KnE Social Sciences, 2025)
The purpose of this study is to study climate change from its various aspects that have a broad impact on the environment. This issue is now a global concern, and it is important to build awareness of the world community in anticipating it. Climate change is characterized by global warming, extreme weather, and various forms of natural disasters that lead to changes in people’s behavior patterns. It also has economic, social, and environmental impacts. The research method of this study is a combination of legislative, conceptual approach, and socio-legal approaches, as well as the harmonization and comparison of various policies and related laws and regulations. The results of the study prove that global cooperation is needed in anticipating this climate change. It requires the development of a comprehensive legal system globally in terms of legal substance, legal structure, and legal culture. However, this paper focuses on building a global legal culture to anticipate climate change and to raise global awareness about the importance of behavioral patterns, consumption patterns, production patterns and lifestyles in anticipating climate change. Building a global legal culture that involves individuals, indigenous peoples, countries, and the world community is a form of anticipating climate change and an effort toward a comfortable life on earth.